Electric power system of Yemen, its structure and characteristics - Ya. S.S. Ali; N. D. Chichirova (Известия высших учебных заведений: Проблемы энергетики)
In this article analysis of the energy system of the Republic of Yemen, its composition and characteristics of the transmission lines, power stations and substations, it also considers the prospects for the development of the power system in the country.